1967
DOI: 10.21236/ad0824795
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Number and Spacing of Elements on the Efficiency of Lasa Beams

Abstract: LASA short-period recordings of 8 teleseismic earthquakes were prefiltered and beamsteered on P-wave arrivals across the 200 km. aperture to establish the relationship between sensor spacing and beam efficiency in terms of noise reduction, signal loss, and S/N ratio improvement. Results show that the combined effect of increasing the number of elements in a beam v,hile simultaneously reducing inter-sensor spacing is to produce progressively less rms noise reduction and S/N gain relative to N. The study further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1972
1972
1974
1974

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The functional flow of data from LASA through the SDAC/LASA system is: 1) data acquisition; 2) detection processing; 3) event processing; 4) experimental operations console (EOC) editing; and 5) publishing of the Daily Earlier studies of the effects of reducing the number of elements at LASA (Hartenberger, 1967;Hartenberger and Van Nostrand, 1970) have shown that the signal-to-noise ratio loss is less than 2db compared to that for the original 525 sensor array when the number of elements is reduced to 119 or 51 with minimum sensor spacing of 3km or 6km respectively. All of the data used in the earlier studies were prefiltered (0.4-3.0 Hz), were beamed to the known opicentral locations, and were corrected for travel-time anomalies (Chiburis, 1968).…”
mentioning
confidence: 99%
“…The functional flow of data from LASA through the SDAC/LASA system is: 1) data acquisition; 2) detection processing; 3) event processing; 4) experimental operations console (EOC) editing; and 5) publishing of the Daily Earlier studies of the effects of reducing the number of elements at LASA (Hartenberger, 1967;Hartenberger and Van Nostrand, 1970) have shown that the signal-to-noise ratio loss is less than 2db compared to that for the original 525 sensor array when the number of elements is reduced to 119 or 51 with minimum sensor spacing of 3km or 6km respectively. All of the data used in the earlier studies were prefiltered (0.4-3.0 Hz), were beamed to the known opicentral locations, and were corrected for travel-time anomalies (Chiburis, 1968).…”
mentioning
confidence: 99%